PERAN PEMERINTAH KELURAHAN DALAM PEMBERDAYAAN MASYARAKAT DI KELURAHAN AIMAS KABUPATEN SORONG - Farida Kalami; Ratna Rosmauli Pakpahan; Arce Yulita Ferdinandus; Susana Magdalena Welly Muskita (Fakultas Ilmu Sosial dan Ilmu Politik, 2023)
The government's role in encouraging community participation is very important for the smooth running of development. To realize community empowerment, prosperity and independence, it needs to be supported by participatory development management. In government settings, honest, open and responsible government behavior is required, while in community settings mechanisms need to be developed that provide opportunities for community participation in the decision-making process and implementation of empowerment programs for the common good. Community empowerment is a process where the community is supported so that it is able to improve its welfare independently. In other words, community empowerment is a process of increasing the ability and attitude of community independence. More specifically, this research wants to look at the role of sub-district government in empowering the community of Aimas sub-district, Sorong district. This research uses qualitative research methods using data collection steps and through observation, interviews and documentation. The results of this research are that the role of sub-district government in empowering the community of Aimas sub-district, Sorong Regency is divided into four roles, namely human development, business development, environmental development and institutional development. This role has been implemented to the maximum extent possible so that there is community participation, even though not everyone is actively involved, apart from that, the results of this research also want to explain the inhibiting factors in carrying out the role of sub-district government in empowering the community of Aimas sub-district, Sorong Regency, namely human resources (community and sub-district employees) which is still less active and lacks supporting infrastructure such as laptops and printers.